Evolution of the Photographic Representation of Women on the Front Pages of the Spanish Press (1977–1997): A Comparative Analysis of ABC and El País - Zafra Arroyo, Ana María (Comunicação e sociedade (Braga.), 2025)
The aim of this research is to analyse the evolution of the photographic representation of women on the front pages of the newspapers ABC and El País, based on a convenience sample of all March issues from 1977 to 1997. The research method used is visual content analysis (Neuendorf, 2017). The units of analysis were obtained from the digital newspaper archives of both newspapers, specifically the front-page archive sections. Of the 1,300 front pages examined, 242 photographs featured women. Beyond the quantitative dimension, the interpretative aspects of visual representation were also considered. This dual approach not only allows for measuring frequencies but also for understanding the cultural and ideological implications of the portrayals. The presence of women on the front pages remains a minority compared to that of men, usually not exceeding 10–15%. Results show that ABC reinforces traditional roles and the decorative representation of women, while El País highlights their political and labour presence, albeit with an emphasis on victimisation. The analysis reveals how these photographs shaped a gendered visual narrative in the press, restricting women’s visibility and recognition in political and professional spheres. Extending these findings to the present, visual stereotypes are shown to persist and to be reproduced not only in digital environments but also in artificial intelligence-generated imagery. O objetivo desta investigação é analisar a evolução da representação fotográfica das mulheres nas primeiras páginas dos jornais ABC e El País, com base numa amostra por conveniência de todas as edições de março entre 1977 e 1997. O método de investigação utilizado foi a análise de conteúdo visual (Neuendorf, 2017). As unidades de análise foram obtidas através dos arquivos digitais dos jornais, especificamente das secções de arquivo das primeiras páginas. Das 1.300 primeiras páginas examinadas, 242 fotografias incluíam mulheres. Para além da dimensão quantitativa, também foram considerados os aspetos interpretativos da representação visual. Esta abordagem dupla permite não só medir frequências, como compreender as implicações culturais e ideológicas das representações. A presença de mulheres nas primeiras páginas continua a ser minoritária em comparação com a dos homens, normalmente não ultrapassando 10–15%. Os resultados revelam que o ABC reforça os papéis tradicionais e a representação decorativa das mulheres, enquanto o El País destaca a sua presença política e laboral, embora com ênfase na vitimização. A análise evidencia como estas fotografias moldaram uma narrativa visual de género na imprensa, restringindo a visibilidade e o reconhecimento das mulheres nas esferas política e profissional. A extrapolação destes resultados para o presente mostra que os estereótipos visuais persistem, sendo reproduzidos não só em ambientes digitais, como também em imagens geradas por inteligência artificial.